2019
DOI: 10.1016/j.tins.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

From Stress to Anhedonia: Molecular Processes through Functional Circuits

Abstract: Converging evidence across species highlights the contribution of environmental stress to anhedonia (loss of pleasure and/or motivation). However, despite a clear link between stress and the emergence of anhedonic-like behavior in both human and animal models, the underlying biological pathways remain elusive. Here, we synthesize recent findings across multiple levels, from molecular signaling pathways through whole-brain networks, to discuss mechanisms through which stress may influence anhedonia. Recent work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 145 publications
4
67
0
1
Order By: Relevance
“…However, this is not surprising, as similar psychopathology across psychiatric conditions is likely to share neuropathogenic mechanisms (Insel et al, 2010). In this vein, it is interesting to consider systemic inflammation as a mediating link between anhedonia and diminished prefrontal activity across psychiatric conditions (Bauer & Teixeira, 2019;Freed et al, 2018;Stanton, Holmes, Chang, & Joormann, 2019). In this regard, anti-inflammatory treatment might be promising in treating anhedonia in some PTSD patients, as preliminary studies have shown it to be efficient in treating subgroups of patients with depression and schizophrenia (Khandaker et al, 2015;Miller & Raison, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this is not surprising, as similar psychopathology across psychiatric conditions is likely to share neuropathogenic mechanisms (Insel et al, 2010). In this vein, it is interesting to consider systemic inflammation as a mediating link between anhedonia and diminished prefrontal activity across psychiatric conditions (Bauer & Teixeira, 2019;Freed et al, 2018;Stanton, Holmes, Chang, & Joormann, 2019). In this regard, anti-inflammatory treatment might be promising in treating anhedonia in some PTSD patients, as preliminary studies have shown it to be efficient in treating subgroups of patients with depression and schizophrenia (Khandaker et al, 2015;Miller & Raison, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Since trauma exposure has been associated with reward processing deficits irrespective of a PTSD diagnosis (Stanton et al, 2019), use of trauma-affected healthy controls (though less affected than the PTSD participants) in this study may conceal any potential effects of the traumatic events per se. Therefore, the results are likely to primarily concern changes in neural activation either related to having experienced multiple traumas and/or the transition from being traumaaffected to developing PTSD.…”
Section: Limitationsmentioning
confidence: 99%
“…There are many theories as to what might cause anhedonia, such as stress [18,19], genetic variations [20••], and dysfunction in brain activity [21,22]. The brain's response to reward during depression is of interest in relation to understanding the causes of anhedonia [23] as it is thought that anhedonia comes about by dysfunctional reward mechanisms in the brain [24].…”
Section: How Might Understanding Reward Illuminate the Symptom Of Anhmentioning
confidence: 99%
“…It is suggested that stress can disrupt reward processing [19], and preclinical work shows that physical stress (e.g. foot shock) decreases consummatory behaviour in rats (decreased saccharine consumption) [42] and exploratory behaviour [43,44].…”
Section: How Might Understanding Reward Illuminate the Symptom Of Anhmentioning
confidence: 99%
See 1 more Smart Citation